ONTOLOGICAL AND AXIOLOGICAL VIEWS ON ETHNOSCIENCE IN RASI - Gita Nurul Puspita; Nahadi; Sjaeful Anwar (Bajang Institute, 2023)
Massive infiltration of foreign cultural influences can threaten the existence of the Indonesian nation's heritage of cultural wisdom. It is necessary to have a learning process that can preserve the culture of our ancestors. One suitable approach for such learning is ethnoscience. Ethnoscience bridges the gap between the natural sciences handed down through generations from ancestors and the scientific knowledge taught in schools. This research aims to analyze the ontological and axiological views of learning with an ethnoscientific approach related to the rasi in junior high school. This study is qualitative research using a literature review. Data collection techniques involve collecting data from books, journal articles, and popular scientific articles. Rasi is a staple food practice for food security in the indigenous people of Kampung Cireundeu, made from cassava (Manihot esculenta). In the process of making rasi, there are scientific concepts that can be integrated into junior high school science learning based on ethnoscience, covering topics such as the Classification of Organism, Simple Machines, Separation of Mixtures, Heat, Physical Changes, Force, Pressure, Nutrition, and Efforts to Maintain Body Health. The ethnoscientific approach supports the achievement of 21st-century skills, including critical thinking, creative thinking, collaboration, communication, character, and citizenship.